Bibliometric Analysis of International Publications Trend on The Taliban - Anisa Indraningtyas; Gonda Yumitro (Pustabiblia: Journal of Library and Information Science, 2022)
This research aims to navigate the result of international publication trends regarding the Taliban for 27 years, starting from 1994 to 2021, utilizing a bibliometric analysis study that analyzed trends in international publications based on quantitative data sources obtained through one of the Scopus data search engines. In addition, bibliometric analysis in this study employed a data visualization software VOSviewer to analyze keywords that often appear in research data regarding the trend of international publications of the Taliban. The findings in this bibliometric analysis study indicated three outcomes. Firstly, numerous international publications on the Taliban as a research topic were navigated, accounting for 1,538 publication documents based on the Scopus data search engine with the keyword "Taliban". Secondly, the results of data visualization on VOSviewer show that the largest keywords visualization are Afghanistan and the Taliban. Lastly, the trend of international publications regarding the Taliban indicated that the highest trend of international publications was in 2010-2011 with publication documents are mainly conducted by researchers in western countries, along with the most funding sponsors were the United States and the United Kingdom. This study concluded that the results of international publication trends regarding the Taliban were influenced by the activities executed by the Taliban receiving global attention throughout time. Hence, the novelty of this study lies in the implementation of bibliometric analysis, presenting a dynamic topic about the Taliban and the data search tools used.